2018
DOI: 10.7819/rbgn.v0i0.3312
|View full text |Cite
|
Sign up to set email alerts
|

How to improve firm performance through employee diversity and organisational culture

Abstract: Purpose -Our study examines the influence that employee diversity has on human resource management (HRM) practices and organisational performance, considering the moderating role of organisational culture, in particular, cultural dimensions such as individualism-collectivism and hierarchical distance.Design/methodology/approach -Through an empirical investigation of 102 Spanish firms using partial least squares-structural equation modelling (PLS-SEM), we evaluated our hypotheses.Findings -Our results show a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, existing literature has broadly focused on the factors that enhance organizational performance. For example, social capital, knowledge sharing, internationalization, knowledge management capabilities, the structural and infrastructural decisions and employee diversity are the factors that enhance organizational performance (Bolat and Yılmaz, 2009;Terry, 2013;Cohen and Olsen, 2015;Espino-Rodríguez and Gil-Padilla, 2015;Ariza-Montes et al, 2017;Triguero-Sánchez et al, 2018). It is hard to find articles on the factors that may undermine organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing literature has broadly focused on the factors that enhance organizational performance. For example, social capital, knowledge sharing, internationalization, knowledge management capabilities, the structural and infrastructural decisions and employee diversity are the factors that enhance organizational performance (Bolat and Yılmaz, 2009;Terry, 2013;Cohen and Olsen, 2015;Espino-Rodríguez and Gil-Padilla, 2015;Ariza-Montes et al, 2017;Triguero-Sánchez et al, 2018). It is hard to find articles on the factors that may undermine organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the control variables related to employees' diversity (Richard et al, 2004;Triguero-S anchez, Peña-Vinces & Guillen, 2018) such as age, gender, and seniority, unfortunately, none of them had the statistical significance that was expected. An explanation that can be considered is that such variables do not have direct effects but rather have mediative effects, which is coherent with previous studies which have shown that employees' diversity variables influence their performance through HRM practices (Triguero-S anchez et al, 2018). However, from an SEM point of view, research model's control variables are adequate in order to understand that 25% of R 2 of TBW is due to both EC and HR, plus control variables.…”
Section: Resultsmentioning
confidence: 93%
“…The team’s human capital emphasizes the heterogeneity [ 71 , 83 , 84 ] and diversity [ 85 , 86 , 87 , 88 ] of employees with different educational backgrounds and professional skills working together. If their different perspectives can help the team measure and manage risk, improve the team’s business vitality, and engender greater team creativity, it will have a positive impact on the enterprise’s total revenue [ 89 , 90 , 91 ]. In addition, employees with different educational backgrounds show different R&D efficiencies, which have different impacts on the cost-effectiveness of R&D expenses, and thus they affect the total revenue of MCEs.…”
Section: Resultsmentioning
confidence: 99%